The Harmonisation and Regionalisation Obligations of The SPS Agreement and The Issues Facing These Obligations - Macfarlane, Abbey-Jean (Department of Commercial Law, 2020)
This dissertation examines the obligations created by Article 3 and Article 6 of the SPS Agreement. It uses Reports accepted by down by the Dispute Settlement Body to find and unpack the interpretation of both Article 3 and 6. These interpretations will be unpacked and examined in detail It further identifies issues and challenges facing these Articles and the obligations which they create. This discussion is held primarily within the context of Developing Country Members. In relation to this discussion policy suggestions will be given forward as possible solutions to certain of the issues and challenges identified. In the course of this discussion the current dispute, which is still in the consultations phase, between Indonesia and Brazil regarding the Importation of Bovine Meat is examined. This paper attempts to provide a probable outcome should this dispute appear before a panel. This outcome relates exclusively to the Article 3 and Article 6 sections of this dispute.